Experimental and theoretical characterization of Bi-based hydroxyapatites doped with Ce. Issue 22 (15th November 2022) - Kareem, Rebaz Obaid; Kaygili, Omer; Ates, Tankut; Bulut, Niyazi; Koytepe, Suleyman; Kuruçay, Ali; Ercan, Filiz; Ercan, Ismail
Abstract: This study deals with the theoretical and experimental characterizations of Bi-based hydroxyapatites (HAps) co-doped with Ce. Five samples of Bi-based HAp (at a constant amount of 0.125 at.%) with additions of the Ce in various amounts (0, 0.125, 0.25, 0.375, and 0.500 at. %) were synthesized by using the wet chemical method. The prepared samples were investigated experimentally by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, differential thermal analysis (DTA), thermogravimetric analysis (TGA), and vibrating sample magnetometer (VSM). All the samples were also modeled by using a density functional theory (DFT), and theoretical results were obtained. Both experimental and theoretical results showed that the lattice parameters and unit cell volume were significantly affected by Ce content. Calculated bandgap energy results of the samples gradually reduced from 4.6308 eV to 4.5299 eV. The bandgap decreased with increasing Ce content, and the densities of states (DOS) values were also affected by the amount of Ce. It was found that the sample doped with 0.500 at. % Ce showed the best biocompatibility among all the as-synthesized samples. The linear absorption coefficient increased with increasing amounts of Ce in all samples, while this parameter decreased with increasing photon energy. The density increases with the increasing Ce content ranging from 3.1615 g cm −3 to 3.1772 g cm −3 . Both crystallite size and crystallinity decreased gradually with the increasing amount of Ce. FTIR and Raman spectra confirm the formation of the HAp structure for all the samples.